Guidelines of the Italian Association of Pediatric Hematology and Oncology for the management of the central venous access devices in pediatric patients with onco-hematological disease. Issue 1 (January 2022) - Cellini, Monica; Bergadano, Anna; Crocoli, Alessandro; Badino, Clara; Carraro, Francesca; Sidro, Luca; Botta, Debora; Pancaldi, Alessia; Rossetti, Francesca; Pitta, Federica; Cesaro, Simone
Introduction: Central venous accesses devices (CVADs) have a fundamental importance for diagnostic and therapeutic purposes in pediatric onco-hematological patients. The treatment of pediatric onco-hematological diseases is complex and requires the use of integrated multimodal therapies. Long-lasting and safe central venous access is therefore a cornerstone for any successful treatment. Methods: The aim of this work is to define pediatric guidelines about the management of CVADs in onco-hematology. A panel of experts belonging to the working groups on Infections and Supportive Therapy, Surgery and Nursing of the Italian Pediatric Hematology Oncology Association (AIEOP) revised the scientific literature systematically, scored the level of evidence and prepared these guidelines. The content of the following guidelines was approved by the Scientific Board of AIEOP. Results and Conclusions: Important innovations have been developed recently in the field of CVADs, leading to new insertion methods, new materials and new strategy in the overall management of the device, especially in the adult population. These guidelines recommend how to apply these innovations in the pediatric population, and are directed to all physicians, nurses and health personnel active in the daily management of CVADs. Their aim is to update the knowledge on CVAD and improve the standard of care in pediatric patients with malignancies.